2024
DOI: 10.1024/0300-9831/a000789
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron and the risk of lung cancer

Abstract: Animal models have suggested the carcinogenic effect of iron due to its oxidative potential. The lung is particularly vulnerable to oxidative stress. However, epidemiological studies investigating the association between dietary iron and the risk of lung cancer have reported inconclusive results. In this systematic review and meta-analysis, we aimed to clarify this association. Methods: We searched PubMed, Web of Science, Scopus and Google scholar for eligible articles published through May 2023 reporting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A systematic review of the mechanistic studies of the link between heme iron intake and risk of colorectal cancer showed that these studies were based on levels of heme iron that were much higher than those in normal human diets, and concluded that there is insufficient evidence to confirm a mechanistic link (94). A meta-analysis of 59 studies (95) showed a borderline significant association between iron intake and colorectal cancer (RR 1.08, 95% CI 1.00-1.17) and no significant association with breast cancer or lung cancer, the latter which was supported by another recent meta-analysis (96). A study based on 1,126 cases and 1,173 matched controls did not show any significant association between serum ferritin concentrations and colorectal cancer (97).…”
Section: Iron and Risk Of Cancermentioning
confidence: 94%
“…A systematic review of the mechanistic studies of the link between heme iron intake and risk of colorectal cancer showed that these studies were based on levels of heme iron that were much higher than those in normal human diets, and concluded that there is insufficient evidence to confirm a mechanistic link (94). A meta-analysis of 59 studies (95) showed a borderline significant association between iron intake and colorectal cancer (RR 1.08, 95% CI 1.00-1.17) and no significant association with breast cancer or lung cancer, the latter which was supported by another recent meta-analysis (96). A study based on 1,126 cases and 1,173 matched controls did not show any significant association between serum ferritin concentrations and colorectal cancer (97).…”
Section: Iron and Risk Of Cancermentioning
confidence: 94%